2010
DOI: 10.1109/titb.2010.2050592
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm of Life Aid (ROLA): An Integrated Sensor System for Supporting Medical Staff During Cardiopulmonary Resuscitation (CPR) of Newborn Infants

Abstract: During the stress of cardiopulmonary resuscitation (CPR), it is difficult to maintain the right rhythm and correct ratio of insufflations to chest compressions and to exert the compressions at a constant pressure. In this paper, we propose and demonstrate an integrated sensor system-the "Rhythm of Life Aid" (ROLA) to support medical staff during CPR of newborn infants. The design concept is based on interactive audio and visual feedback with consideration of functionalities and user friendliness. A prototype R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Our study found similar results with high inter-individual variation in CC force and rate already in the first minute of simulated CPR. To overcome inconsistencies in CC delivery, Andriessen et al [11] used a “Rhythm of life aid” (ROLA) [12] feed forward and feedback device on a manikin during simulated neonatal CPR and reported that 3:1 C:V CPR with the ROLA device resulted in CC with greater pressure and less variability compared to CPR without ROLA. In addition, using the ROLA device resulted in a more consistent CC rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found similar results with high inter-individual variation in CC force and rate already in the first minute of simulated CPR. To overcome inconsistencies in CC delivery, Andriessen et al [11] used a “Rhythm of life aid” (ROLA) [12] feed forward and feedback device on a manikin during simulated neonatal CPR and reported that 3:1 C:V CPR with the ROLA device resulted in CC with greater pressure and less variability compared to CPR without ROLA. In addition, using the ROLA device resulted in a more consistent CC rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of health monitoring, another integrated sensor system is proposed to support medical staff during cardiopulmonary resuscitation (CPR) of newborn infants. In this system, a prototype rhythm of life aid (ROLA) device was built, consisting of a transparent foil integrated with pressure sensor and electroluminescent foil actuators for indication of the exerted chest compression pressure, as well as an audio box to generate distinctive sounds as audio guidance for insufflations and compressions [ 45 ]. The clinicians can make appropriate adjustments during CPR according to the feedback from the audio signal buzzer and the visual actuator.…”
Section: Methods or Techniques In Wearable Sensor Systems For Infantsmentioning
confidence: 99%
“…The ROLA device features a box that generates an audio-prompted rate guidance with distinct sounds for inflations and compressions (feed forward), and a transparent sheet that was integrated with a visual actuator that lights up as the pressure on the foil is increased (feedback) [7]. The design features clear recognizable marks to be placed over sternum and inter nipple line in order to position the point of chest compressions exactly in the middle of the lower sternum (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assist neonatal resuscitation we designed a device, called “Rhythm of life aid” (ROLA) that supports health care providers during CPR of the newborn. In a previous paper we have described in detail the design and technical aspects of the device [7]. The specific research questions that we asked for this study were: (a) Does the use of ROLA lead to consistent CPR with respect to the rhythm and 1:3 ratio of inflations and compressions?…”
Section: Introductionmentioning
confidence: 99%